Respuesta :

Answer:

( x - (-1) )^2 + ( y - (-1) )^2 = 3^2

Step-by-step explanation:

The equation of a circle is ( x - h )^2 + ( y - k )^2 = r^2, r is the radius.

(h,k) is the coordinates for the center point.

In this image, it appears K is 3 units away from any point on the circle, making 3 the radius.

Our equation is now ( x - h )^2 + ( y - k )^2 = 3^2

Now, we need to find the coordinate of K; the center point.

K's x is -1 and K's y is also -1.

Our equation is now:

( x - (-1) )^2 + ( y - (-1) )^2 = 3^2

ACCESS MORE